Family Financial Planning Training for a Group of Pkk Women in Labuh Baru Barat District - Prihastuti, Asepma Hygi; Wahyuni, Sri; Adriyani, Annesa; Ramadhani, Suci; Zainal, Rahmi (Pasundan Community Service Development, 2023)
This community service activity is carried out because mothers as managers of family finances are expected to be careful in planning their family finances, so that they can avoid wasting money, prioritize fulfilling needs rather than desires, and not live by always relying on debt, because expenses are greater than income. , and can set aside money for savings/investment. This training was carried out for 24 PKK mothers in Labuh Baru Barat Subdistrict, before being given material and training regarding family financial planning, a Pre Test was carried out with the results.14 people have not managed their finances well, 6 people have only recorded family expenses, and 4 people have recorded household financial income and expenses. This shows that the family's financial planning is still not good, so sometimes for sudden financial needs they often take out loans by digging holes to cover holes. After that, materials and training were provided, then as an evaluation a Post Test was carried out, the results of which stated that 20 people could understand the difference between needs and wants, 18 people could calculate the entire family income, 21 people could make a list of priority expenses, 15 people could maintain the debt ratio , and 12 people can allocate Savings, Insurance and Investment. It is hoped that by carrying out this family financial planning training, PKK mothers will be able to plan their finances well, be able to make a budget for household income and expenditure, and be able to save/invest for other needs in the future, so that a prosperous family can be achieved.